PENGARUH DIMENSI FRAUD TRIANGLE TERHADAP PERILAKU KECURANGAN AKADEMIK PADA MAHASISWA AKUNTANSI (Studi Pada Mahasiswa Prodi Akuntansi di Perguruan Tinggi Kota Malang) - Erlinliya Motifasari; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
ABSTRACTThis research was conducted with the aim of knowing the effect of fraud triangle on academic fraudulent behavior in Accounting Students at Malang University. This study uses a quantitative method by distributing questionnaires directly to respondents. The population used is accounting students in Malang. Sampling uses purposive sampling, namely the technique of determining the sample with certain considerations. Data analysis in this study used multiple linear regression models with SPSS analysis tools. The results showed that pressure, opportunity and rationalization at the same time had a significant effect on academic cheating behavior on students. And partially, pressure has a significant effect on academic cheating behavior on students, opportunities have a significant effect on academic cheating behavior on students, and rationalization has a significant influence on academic cheating behavior on students.Keywords: Pressure, Opportunity, Rationalization, and Academic Fraud